2009
DOI: 10.1002/chem.200901703
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Inclusion Behaviour and Framework Structures in Organic Crystals

Abstract: Day, (2010) Modelling organic crystal structures using distributed multipole and polarizability-based model intermolecular potentials. Physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 40 publications
1
63
0
1
Order By: Relevance
“…It has been shown before that stable inclusion structures tend to be located along the low energy edge of crystal structure landscapes, where structures occupy their lowest energy configuration for a given packing 11 density. 41 Here, we observe that the calculated energy of the highly porous TCC1-R structure stands out on the landscape (Fig. 5a) as unusually stable for such a low density packing mode of this molecule.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…It has been shown before that stable inclusion structures tend to be located along the low energy edge of crystal structure landscapes, where structures occupy their lowest energy configuration for a given packing 11 density. 41 Here, we observe that the calculated energy of the highly porous TCC1-R structure stands out on the landscape (Fig. 5a) as unusually stable for such a low density packing mode of this molecule.…”
mentioning
confidence: 59%
“…25) where the nanotubes are preserved, but where collapse of the cage occurs. The bulk TCC2-R/TCC2-S material was insufficiently crystalline to determine whether the loss of porosity was due to this cage collapse, to a loss of crystallinity, or to both.We also calculated the landscapes of possible crystal structures of enantiopure and racemic TCC1-TCC3 using crystal structure prediction (CSP) 21,39,40,41,42 methods (Fig. 5, Supplementary Information, Section 4.6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…J (339_ P 4 2 / n , Z ′ = 2) and tetr. I (22_ P 4 2 / n , Z ′ = 2), have voids 79 of a size that could accommodate more water, but this void space is mainly surrounded by hydrophobic regions and so seem unlikely to be a hydrate framework.…”
Section: Resultsmentioning
confidence: 99%
“…However, Cruz-Cabeza and co-workers demonstrated that the observed frameworks of inclusion crystals are also located on predicted crystal energy landscapes, at higher energies, but along the lowenergy edge of energy-density distribution of crystal structures. 45 The identification of stable, low density structures among CSP structures has the promise of predicting clathrate structures, 46 but also of desolvatable extrinsically porous crystals. Indeed, CSP was recently used to computationally assess a series of awkwardly-shaped benzimidazolones and imides for likely porous structures, finding that some molecules featured 'spikes' of unusually low energy structures in the low density region of their structural landscapes.…”
Section: 37mentioning
confidence: 99%